2002
DOI: 10.1123/jab.18.4.345
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age, Gender, and Obesity on the Mechanical Properties of the Heel Pad under Walking Impact Conditions

Abstract: Impact mechanics of the human heel pad were studied using a ballistic pendulum. Young and elderly men and women took part in the experiment. Twelve parameters were used to describe heel pad properties. Analysis of variance was conducted to assess the influence of age, gender, and obesity. Heel pad properties were correlated with impact force and time to peak force in order to study impact mechanics. Maximal stiffness, peak displacement, and energy absorption were established so as to sufficiently describe impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Of the six studies that assessed foot structure, there were two measures of foot posture that were associated with obesity; that of changes in heel pad properties and planus (low-arched) foot structure. Changes in heel pad properties in obese participants were found to have a large effect size, although this variable was assessed in only one study (27). Two previous systematic reviews (11,53) of foot pain in adults have advised caution interpreting the strength of associations where less than three studies are identified.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Of the six studies that assessed foot structure, there were two measures of foot posture that were associated with obesity; that of changes in heel pad properties and planus (low-arched) foot structure. Changes in heel pad properties in obese participants were found to have a large effect size, although this variable was assessed in only one study (27). Two previous systematic reviews (11,53) of foot pain in adults have advised caution interpreting the strength of associations where less than three studies are identified.…”
Section: Discussionmentioning
confidence: 94%
“…The Quality Index tool allows for assessment of internal and external validity, reporting and statistical power. It consists of 27 items, of which 12 were excluded , as they were not relevant to non‐intervention studies. Item 10 was also omitted for those studies that did not report probability values, and items 5, 21 and 22 were omitted for studies that did not include a control group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obesity impact was small to low. Age, gender and obesity have been shown to introduce significant differences in heel properties (Alcantara et al, 2012). Forefoot and heel width have shown the impact of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific opinions vary regarding how body composition (body fat and other components) affects the feet. It is believed that body fat mass, rather than changes in foot morphology and structure, may be the cause of an increased mid-foot contact area and, ultimately, fallen arches (Alcantara, Forner, Ferrus, Garcia, & Ramiro, 2012;Butterworth et al, 2014;Wearing et al, 2004). The strength of association between body composition components and foot morphology and structure, likewise foot function, is still unclear (Butterworth et al, 2014).…”
Section: Introductionmentioning
confidence: 99%